Phenotypic variation of wild Chamomile (Matricaria chamomilla L.) populations and their evaluation for medicinally important essential oil - Tsivelika, Nektaria; Sarrou, Eirini; Gusheva, Katerina; Pankou, Chrysanthi; Koutsos, Theodoros; Chatzopoulou, Paschalina; Mavromatis, Athanasios (Biochemical systematics and ecology, 2018)
In this study the existing phenotypic and chemotypic variability of native to Greece chamomile populations was investigated, aiming to select the appropriate ones for the production of high quality essential oil. For this purpose, eleven native chamomile populations were studied concerning the main constituents of the essential oil (a-bisabolol and chamazulene), and a pre-breeding evaluation experiment was initiated, setting up as main target the essential oil composition and agronomical traits. The two most remarkable populations were further assessed, in comparison to five commercial chamomile varieties, through a honeycomb arrangement in the field. The results showed that, the native populations were classified in lower levels concerning morphological and agronomical traits; however they exhibited high stability for the agronomical characteristics evaluated, in comparison with those of the commercial varieties. Furthermore, the essential oil of the selected native germplasm revealed values up to 32.6% for a-bisabolol and 15.3% for chamazulene, approaching or even exceeding the corresponding values of most of the commercial varieties. According to these results it can be concluded that a promising native germplasm can be exploited for further breeding purposes, to produce a new cultivar with medicinally important essential oil composition. [Display omitted] •Phytochemical evaluation of native to Greece chamomile populations.•Exemplify superior germplasm and comparison with commercial chamomile varieties.•Selection of native populations with high a-bisabolol and chamazulene content.•Use of honeycomb design for agro-morphological evaluation.